2014
DOI: 10.1099/ijs.0.059527-0
|View full text |Cite
|
Sign up to set email alerts
|

Janibacter indicus sp. nov., isolated from hydrothermal sediment of the Indian Ocean

Abstract: A Gram-staining-positive, aerobic and non-motile strain, 0704P10-1 T , was isolated from hydrothermal sediment of the Indian Ocean. Phylogenetic, phenotypic and chemotaxonomic data for the organism supported that it belonged to the genus Janibacter. Strain 0704P10-1 T showed 97.2-98.7 % 16S rRNA gene sequence similarities to the type strains of recognized members of the genus Janibacter. It contained meso-diaminopimelic acid as the diagnostic diamino acid in the cell wall. MK-8(H 4 ) was the only menaquinone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…ZCA4 was an endosporeforming bacterium. These observations are in agreement with those of Bacillus filamentosus SGD-14 T (Sonalkar et al, 2015), Janibacter indicus 0704P10-1 T (Zhang et al,2014), and Brevibacterium casei NCDO 2048 (CMD1) (Collins et al,1983).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…ZCA4 was an endosporeforming bacterium. These observations are in agreement with those of Bacillus filamentosus SGD-14 T (Sonalkar et al, 2015), Janibacter indicus 0704P10-1 T (Zhang et al,2014), and Brevibacterium casei NCDO 2048 (CMD1) (Collins et al,1983).…”
Section: Resultssupporting
confidence: 90%
“…These testers can be used to easily differentiate between the strains. The observation that ZCA4 consumed an array of different carbon and nitrogen sources is in general agreement with that reported for B. filamentosus SGD-14 T (Sonalkar et al,2015), J. indicus 0704P10-1 T (Zhang et al,2014), and B. casei NCDO 2048 (CMD1) (Collins et al,1983). However, some differences do exist between our strains and the relevant type strains.…”
Section: Phenotypic Characteristics Of the Isolated Strainssupporting
confidence: 91%
“…Since the genus Janibacter , a member of the family Intrasporangiaceae , was first described by Martin et al, a total of nine species have been identified including J. limosus , Janibacter terrae , Janibacter melonis , Janibacter anophelis , Janibacter corallicola , J. hoylei , Janibacter alkaliphilus , J. cremeus , and Janibacter indicus . Gram stains for these strains are Gram‐variable or Gram‐positive with coccoidal to rod forms in singles, pairs, or irregular clumps .…”
Section: Discussionmentioning
confidence: 99%
“…Gram stains for these strains are Gram‐variable or Gram‐positive with coccoidal to rod forms in singles, pairs, or irregular clumps . Although the natural habitat is not fully understood, members of the genus Janibacter have been recovered from various environments including environmentally polluted samples, melon, the midgut of mosquitoes, coral, sea sediment, and an air sample . Among Janibacter spp., J. hoylei was first isolated from cryotubes used to collect air samples in the upper atmosphere at an altitude of 40–41.4 km and was named after Sir Fred Hoylei, the renowned English astronomer, in 2009 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation